International perspectives on supporting and engaging online learners - Hoffman, Jaimie; Blessinger, Patrick (Emerald Publishing Limited, 2021)
The COVID-19 pandemic has accelerated growth in online education across the world. While the online classroom experience has been written about extensively, the outside of class experience and student services for those learning remotely has received little attention. This book provides College and university personnel with research, theoretical foundations, and best practice to support and engage online learners.In this edited collection, authors from across the globe present case studies in various contexts including a large state university system, a growing public master's degree, two private institutions, and a Scottish institution. Various theoretical constructs are provided to help inform practices for supporting online students including Wenger's 'communities of practice', Garrison's 'communities of inquiry', and the Dynamic Student Development Metatheodel. Understanding that all students encounter different challenges, the volume also covers the different needs of specific student populations throughout their online experiences and concludes with a discussion about the importance of inclusion for students with disabilities.
Includes index.
Keywords: Internet in higher education.; Telecommunication in higher education.; Distance education.; Education -- Higher.; Higher & further education, tertiary education.; elektronické knihy; electronic books